A família que cuida do indivíduo em sofrimento psiquíco: um estudo fenomenológico - Lacchini, Annie Jeanninne Bisso (2011)
Psychic suffering and the body language of family members result from symbolic meanings, whose significations are apprehended through human relationships, and that are given to the interpretation of the situation which is influenced by the interaction of the family members with each other and with the society. This study aimed to understand the meanings of care to the family of the individual experiencing psychic suffering. This research is a qualitative study with a phenomenological approach based on Maurice Merleau-Ponty s theoretical and philosophical framework of reference and on the hermeneutic phenomenology of Paul Ricoeur. Following the approval by the Human Research Ethics Committee of the institution under the Protocol Nº 0214.0.243.000-09, phenomenological interviews were conducted between October 2009 and June 2010 with 14 family caregivers of individuals presented with psychic suffering who were admitted at Paulo Guedes Unit of Psychiatric Admission of the University Hospital of Santa Maria/RS/Brazil. The following guided question was made in the interview: what is it like to take care of (patient s name)? From the comprehension and interpretation of the speeches, three themes emerged: the world of the family that provides healthcare; his or her own perception as a caregiver, and perceiving the other in the world of care. This research made it possible to understand that the family members showed that the care given to the other is on the intertwinement of the being with the world. There are several difficulties regarding the caregiving of an individual experiencing psychic suffering when he or she is not hospitalized, and the main are as follows: the fact that the family member had practically to abdicate of his or her own life to take care of the other revealing that caregiving is related to a historicity of a customary body situated in a space and time. These considerations can serve as subsidies for nurses formation and education so as to keep searching for strategies of sensibilization and mobilization in the academic field as well as providing opportunities to new learning spaces which are in line with the Psychiatric Reform. Also, professionals of the nursing staff should reflect on the caregiving beyond the hospital scenario supporting the family caregiver in home care environment.